2018
DOI: 10.1371/journal.pone.0197464
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal human antibodies against glycans bearing red meat-derived non-human sialic acid N-glycolylneuraminic acid are stable, reproducible, complex and vary between individuals: Total antibody levels are associated with colorectal cancer risk

Abstract: BackgroundN-glycolylneuraminic acid (Neu5Gc) is a non-human red-meat-derived sialic acid immunogenic to humans. Neu5Gc can be metabolically incorporated into glycan chains on human endothelial and epithelial surfaces. This represents the first example of a “xeno-autoantigen”, against which circulating human “xeno-autoantibodies” can react. The resulting inflammation (“xenosialitis”) has been demonstrated in human-like Neu5Gc-deficient mice and contributed to carcinoma progression via antibody-mediated inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 85 publications
2
53
0
Order By: Relevance
“…S8G). This is likely because the polyclonal antibody response is extremely complex and variable between individuals, and no single epitope can be easily correlated with disease (43). In general, we show that the immune response to the metabolically incorporated foreign Neu5Gc in Gc-immunized Cmah −/− Ldlr −/− mice fed a Neu5Gc-rich HFD was significantly correlated with the increased atherosclerosis development.…”
Section: Loss Of Cmah Results In Enhanced Inflammatory Macrophages Andmentioning
confidence: 77%
See 1 more Smart Citation
“…S8G). This is likely because the polyclonal antibody response is extremely complex and variable between individuals, and no single epitope can be easily correlated with disease (43). In general, we show that the immune response to the metabolically incorporated foreign Neu5Gc in Gc-immunized Cmah −/− Ldlr −/− mice fed a Neu5Gc-rich HFD was significantly correlated with the increased atherosclerosis development.…”
Section: Loss Of Cmah Results In Enhanced Inflammatory Macrophages Andmentioning
confidence: 77%
“…The Combination of Human-Like Anti-Neu5Gc Antibodies and Neu5Gc-HFD Further Increases Atherogenesis in Cmah −/− Ldlr −/− Mice. Due to the lack of Neu5Gc production most humans develop circulating anti-Neu5Gc antibodies (42,43). Unlike humans, Cmah −/− Ldlr −/− mice do not spontaneously produce anti-Neu5Gc antibodies even after long-term feeding of Neu5Gc-rich chow (44).…”
Section: Loss Of Cmah Results In Enhanced Inflammatory Macrophages Andmentioning
confidence: 99%
“…All MOAs: Notwithstanding any of the four MOA, the result is the same: food ingredients can interact with the human GI mucosae and/or cross the intestine barrier into the blood stream. Specifically, glycans can be absorbed by cells and circulate in the body [9]. Several studies demonstrated AGA are found in the blood of non-allergic donors, confirming food glycans can cross the barrier [168].…”
Section: Glycan Reactionsmentioning
confidence: 99%
“…Because of their unique chemical properties, glycans have unsurpassed structural variability, and enormous changeability beyond the simple sequence, as for proteins or nucleic acids [7]. The presence of an anomeric carbon atom, the possibility of linkage formation involving different acceptor sites and the ring size with frequent occurrence of branching and site-specific modifications allows glycans to display unique properties [8,9]. Hence, it can be stated that the proteosome and the nucleosome are no match for the glycome, as the coding capacity of the oligosaccharide language is simply orders of magnitude higher [10].…”
Section: Introductionmentioning
confidence: 99%
“…The proposed causal role of anti-Neu5G in inducing tumors in mice [ 17 ] is speculative in humans. Although no difference was observed using ELISA, higher anti-Neu5Gc binding synthetic Neu5Gc glycans have been recently reported in a series of 71 patients with colon carcinoma [ 19 ]. These findings did not attain statistical power and the proposed causal role of Neu5Gc accumulation in tumors [ 5 ] remains speculative.…”
mentioning
confidence: 99%